Private Bond Restructurings : Lessons for the Case of Sovereign Debtors - Pinon-Farah, Marco (IMF Working Papers; Working Paper, 1996)
This paper reviews recent experience with both sovereign and private bond restructurings. It also summarizes the literature on private bond restructurings and describes the 'typical' process for a voluntary exchange of new bonds for existing obligations. From this information some conclusions are drawn as to the possibility of concluding voluntary restructuring agreements for sovereign bonds within relatively short periods of time.